Phantom borders and electoral behaviour in Poland. Historical legacies, political culture and their influence on contemporary politics - Jańczak, Jaroslaw (ERDKUNDE, 2015)
The article deals with phantom borders in electoral behavior in Poland. Being aware of the already wide literature in this field, the author tries to fill a gap existing in the research by investigating scale as a factor determining phantom borders’ construction. Two historical-administrative regions, Wielkopolska and Pomorze (crossed by relict boundaries) were tested quantitatively and qualitatively. By employing double de-scaling (territorial and electoral) the author discovered that in both the macro and micro scales phantom borders are present, however, their construction and manifestation differs significantly. Consequently, this finding brings a new perspective to phantom border studies, widening the currently dominating historical perspective (with its structural and normative dimensions) by adding a new element: scale. It seems to bring a new perspective in understanding the investigated processes.